2012
DOI: 10.1590/s0100-736x2012001200006
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização do controle de Haematobia irritans e Rhipicephalus (Boophilus) microplus no Triângulo Mineiro e Alto Paranaíba, Minas Gerais

Abstract: Pesq. Vet. Bras. 32(12):1246-1252, dezembro 2012 1246 RESUMO.-O controle eϐicaz de Haematobia irritans (mosca--dos-chifres) e Rhipicephalus (Boophilus) microplus (carrapato-do-boi) é um fator crucial à maior rentabilidade da pecuária brasileira, porém ainda constitui-se um desaϐio. Um maior conhecimento das práticas adotadas no combate destes parasitos faz-se necessário para que se possam estruturar estratégias de controle mais próximas da realidade do produtor rural e mais fáceis de serem executadas. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…This is important information, since the chemical products for controlling these two parasites are similar. Farias et al (2008) and Santos et al (2009) found a similar situation in Rio Grande do Sul and Domingues et al (2012) in Minas Gerais. Care is required with regard to cross-selection for the two parasites.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This is important information, since the chemical products for controlling these two parasites are similar. Farias et al (2008) and Santos et al (2009) found a similar situation in Rio Grande do Sul and Domingues et al (2012) in Minas Gerais. Care is required with regard to cross-selection for the two parasites.…”
Section: Discussionsupporting
confidence: 56%
“…The lack of any habit of using individual protection devices and the low degree of concern about poisoning from acaricide applications were also observed by Rocha et al (2006), Bertolucci (2010) and Domingues et al (2012) on farms in Minas Gerais and by Bello (2010) on farms in Rio de Janeiro. Cattle need to be restrained in order to do a good acaricide application, especially in relation to the ventral area of the animals, where most of the ticks are attached .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A utilização de produtos organofosforados parece ser indício de resistência aos piretroides e da necessidade de mudança do produto usado para controle [14]. Organofosforados apresentaram 100% de eficácia no controle da mosca, quando utilizados brincos impregnados com 40% de diazinon com melhora no ganho de peso, pois animais livres de estresse e espoliação parasitária dispendem maior tempo na alimentação [41].…”
Section: Discussionunclassified
“…Cattle kept under field conditions tend to be parasitized simultaneously by different species of ectoparasites. Proposals to combat more than one parasite at once are more economical and more operationally feasible and may have greater acceptance by farmers [ 3 ]. Most control programs are based primarily on the application of ectoparasiticides.…”
Section: Introductionmentioning
confidence: 99%